2009
DOI: 10.2478/s11687-009-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

First record of Steinernema feltiae (Filipjev) (Rhabditida: Steinernematidae) in Slovenia

Abstract: In October 2007 we examined 80 soil samples from 16 different locations in the central part of Slovenia (the Notranjska region) and confirmed the presence of entomopathogenic nematodes only in two soil samples. This represents the first recorded instance of an entomopathogenic nematode in Slovenia. In sample B30 we confirmed the presence of Steinernema feltiae (Rhabditida: Steinernematidae) by means of a molecular technique. In Slovenia the application of entomopathogenic nematodes was hitherto possible only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
5
11
0
1
Order By: Relevance
“…However, we should point out that the low recovery rate is not unusual, as other surveys have also recorded similar low rates (Hazır et al, 2001). For instance, similar results were obtained in the research of Laznik et al (2009a), where they confirmed the occurrence of EPNs in Slovenian soils in only 2.5% of soil samples. The occurrence of steinernematids and heterorhabditids in most of the surveyed areas indicates the potential role of nematodes in natural regulation of insect populations.…”
Section: Discussionsupporting
confidence: 74%
“…However, we should point out that the low recovery rate is not unusual, as other surveys have also recorded similar low rates (Hazır et al, 2001). For instance, similar results were obtained in the research of Laznik et al (2009a), where they confirmed the occurrence of EPNs in Slovenian soils in only 2.5% of soil samples. The occurrence of steinernematids and heterorhabditids in most of the surveyed areas indicates the potential role of nematodes in natural regulation of insect populations.…”
Section: Discussionsupporting
confidence: 74%
“…Some researchers report that S. feltiae, S. intermedium and S. affine are likely to appear on cultivated land (Sturhan, 1996). In our study we came to a similar conclusion only in one of the positive samples (the strain B30, which was found on a field near Cerknica), while all other strains were found on uncultivated areas (forests, meadows) (Laznik et al, 2009a). In Europe S. feltiae has been so far confirmed in 24 countries and is considered one of the most widely spread species of EPNs (Hominick, 2002).…”
Section: Steinernema Feltiae (Filipjev)supporting
confidence: 48%
“…The most frequently (15 positive samples) encountered species of EPNs in Slovenia was Steinernema feltiae (Filipjev) (accesion no: EU914855; http://blast.ncbi.nlm.nih.gov/Blast.cgi) (Laznik et al, 2009a). In Slovenia it was found in Notranjska, Dolenjska and Prekmurje.…”
Section: Steinernema Feltiae (Filipjev)mentioning
confidence: 99%
“…This is in agreement with the earlier studies. S. feltiae has been found as the most common EPNs species isolated in the other surveys conducted in Turkey, followed by H. bacteriophora (Laznik et al 2009;Canhilal et al 2016 andCanhilal et al 2017). Both of these EPNs are widely distributed throughout the world.…”
Section: Resultsmentioning
confidence: 95%